Rhubarb Enema Improved Colon Mucosal Barrier Injury in 5/6 Nephrectomy Rats May Associate With Gut Microbiota Modification - Ji, Chunlan; Deng, Yusheng; Yang, Aicheng; Lu, Zhaoyu; Chen, Yang; Liu, Xusheng; Han, Lijuan; Zou, Chuan (Frontiers in Pharmacology, 2020)
Chronic kidney disease (CKD) is often accompanied with colon mucosal barrier damage and gut microbiota disturbance, which strongly associate with up-regulated inflammation and kidney tubulointerstitial fibrosis. However, few interventions could protect the damaged barrier effectively. Rheum palmatum L or rhubarb is a common herbal medicine which is widely used to protect the colon mucosal barrier. In previous studies, we found that rhubarb intervention may reduce renal inflammation and tubulointerstitial fibrosis, via gut microbiota modification. However, whether intestinal barrier function could be improved by rhubarb intervention and the relationship with intestinal flora are still unknown. Therefore, we investigated the effects of rhubarb enema on intestinal barrier, and further analyzed the relationship with gut microbiota in 5/6 nephrectomy rats. Results indicated that rhubarb enema improved the intestinal barrier, regulated gut microbiota dysbiosis, suppressed systemic inflammation, and alleviated renal fibrosis. More specifically, rhubarb enema treatment inhibited the overgrowth of conditional pathogenic gut bacteria, including Akkermansia, Methanosphaera, and Clostridiaceae in CKD. The modification of gut microbiota with rhubarb intervention displayed significant correlation to intestinal barrier markers, TLR4–MyD88–NF-κB inflammatory response, and systemic inflammation. These results revealed that rhubarb enema could restore intestinal barrier by modifying several functional enteric bacteria, which may further explain the renal protection mechanism of the rhubarb enema.